Biological activity of secondary metabolites produced by a strain of Pseudomonas fluorescens - Boruah, H P Deka; Kumar, B S Dileep (Folia microbiologica, 2002)
Biological activity of secondary metabolites produced by a plant-growth-promoting Pseudomonas fluorescens was evaluated. The strain produced antibiotics phenazine (PHE), 2,4-diacetylphloroglucinol (PHL) and siderophore pyoverdin (PYO) in standard King's B and succinic acid media, respectively. After extraction, PYO was identified by comparing the UV-spectra and moss-green color development after 'diazotized sulfanilic acid' (DSA) spray in TLC. PHE and PHL were identified by comparing standard compounds on TLC and orange-color development immediately after DSA spray. In vitro antibiosis study of the metabolites revealed their antibacterial and antifungal activity against bacterial test organisms Corynebacterium sp., Mycobacterium phlei and M. smegmatis and test fungi Fusarium moniliforme, F. oxysporum, F. semitectum, F. solani and Rhizoctonia solani. A statistically significantly higher plant growth was recorded in siderophore-amended plantlets under gnotobiotic conditions whereas PHE and PHL did not show any plant-growth-promoting activity. These results support the importance of the secondary metabolites produced by the strain P. fluorescens in enhancing plant growth and in controlling fungal and bacterial pathogens.
Keywords: Plants; Fungi; Phenazines; antifungální látky; Oligopeptides; Germ-Free Life; Plant Development; Plant Growth Regulators; houby; fenaziny; vývoj rostlin; antibakteriální látky; biologické pigmenty; oligopeptidy; Phloroglucinol; Pigments, Biological; regulátory růstu rostlin; Anti-Bacterial Agents; Antifungal Agents; floroglucinol; Siderophores; gnotobiologické modely; Bacteria; siderofory; Pseudomonas fluorescens; rostliny